Strangers and neighbours: cross-border banking in North America - DEAN, J.W.; GIDDY, I. (PSL Quarterly Review, 2013)
The paper is concerned with regulatory and competitive aspects of the mutual penetration by Canadian and U.S. banks of each other’s domestic markets. The authors assess the degree to which economic factors alone are responsible for the difference in growth rates between domestic and foreign banks in North America. They argue that regulation has not affected the growth of foreign banks in North America by addressing the question of reciprocity in banking regulations, before examining foreign banks in the U.S. and the manner in which they have been regulated. U.S. banks operating in Canada are then dealt with. Finally, the results of an empirical test of the proposition that the growth of cross-border banking is attributable to factors other than differential regulation is presented. JEL: G21